Ambipolar charge transport in a bis-diketopyrrolopyrrole small molecule semiconductor with tunable energetic disorder. Issue 3 (22nd December 2017) - Zhou, Jiyu; Bi, Shiqing; Yang, Shuo; Zhou, Huiqiong; Zhang, Yuan
Abstract : Energetic disorder and activation energy in ambipolar OFETs based on a small molecule BTDPP2 are tuned by its crystallinity. Abstract : Energetic disorder and activation energy are important parameters that influence the charge carrier mobility in organic semiconductors. Herein, we investigate temperature-dependent ambipolar charge transport alongside its thermal activation energy in organic field-effect transistors (OFETs) based on a diketopyrrolopyrrole (DPP) based small molecule BTDPP2. The determined energetic disorder in BTDPP2 is analogous to those of highly crystalline molecules, such as pentacene, while lower than those of widely used fullerene derivatives (PCBM) or semi-crystalline polymers, such as P3HT. We demonstrate that the energetic disorder and activation energy in BTDPP2 are both impacted by the crystallinity, which is tuned by thermal annealing; moreover, to a certain extent, these two parameters can reduce with increasing the structural order. Moreover, the energetic disorder tends to decrease when BTDPP2 is subjected to thermal annealing. Through comparing the electron transport in BTDPP2 based OFETs and vertical diodes, in which the electron densities differentiate substantially, the different activation energies are roughly described in terms of achievable carrier densities in these two devices. To the best of our knowledge, this aspect has not been addressed on the electron transport in molecular semi-conductive materials. Our results shine light on fundamental understandings of charge transport properties in solution processed small molecules holding promise for opto-electronic applications.